Mapping human health risks from ecosystems (EHRs) based on vegetation census data - Chengji Shu; Wengbo Cai; Manlin Zhang; Chenyang Guo; Li Lin; Zhiyun Ouyang (Ecological Indicators, 2024)
Ecosystem benefits and services assessments are widely used in the current urban ecological management strategies to enhance benefits of ecosystems to urban residents, but ecosystems are not benign entities that exist solely for human benefit. Plagues, diseases, and other ecosystem-generated health risks (EHRs) have caused huge losses of life and property. In promoting systematic and comprehensive urban development and the quality of life for residents, Risk reduction for EHRs cannot be ignored. As existing studies of EHRs mapping remain relatively few. This paper proposed a mapping method based on vegetation census data for two EHRs: human-bat contact infection risk (HBCIR) and human-pollen contact sensitization risk (HPCSR). Results showed that: (1) The bat distribution risk (SBR) and the pollen sensitizing plant distribution risk (ROSDmean) were higher in woodlands and areas around reservoirs where habitat conditions are better across the city. (2) The areas with higher HBCIR and HPCSR were mainly located in the central and western parts of Shenzhen, especially in the surrounding densely populated areas with better habitat conditions. (3) All streets differed significantly from each other in HBCIR and HPCSR distribution characteristics, three streets, Huafu, Meilin and Donghu, had higher risk values. The results can provide guidance to policymaker in their work on biodiversity conservation, health risk control, and tree species application. Additionally, the methodology adopted in this study may inspire future researches on the spatialization of other EHRs.